Entrepreneurs' Personal Values and Green Business Culture: A Qualitative Study of Indonesian MSMEs - Wulandari Sungkowo Tri Putri (Generate Digital Publishing, 2025)
Objectives: This study aims to explore the role of entrepreneurs' personal values in fostering a green business culture among Indonesian Micro, Small, and Medium Enterprises (MSMEs). This study aims to understand how moral, social, and spiritual beliefs influence organizational transformation towards sustainability oriented business practices. Research Design & Methods: This study uses a qualitative exploratory case study involving 18 MSME groups (178 members) across Indonesia, using purposive sampling. Data gathered through interviews, observations, and document analysis were thematically analyzed. Findings: The findings reveal that personal values such as responsibility towards nature, gratitude to God, honesty, and social awareness serve as the foundation for sustainable entrepreneurship. These values evolve from individual ethics into collective norms that shape organizational culture. The internalization of these values is manifested in environmentally friendly production, resource efficiency, waste reduction, and community empowerment. The results also show multidimensional impacts: economic (cost efficiency and increased product value), social (strengthened solidarity and environmental awareness), and ecological (waste reduction and natural resource conservation). Implications & Recommendations: Sustainable transformation in MSMEs requires not only financial or regulatory support but also moral and cultural reinforcement through value -based education, ethical leadership, and community-driven sustainability efforts.